(untitled) (Nordic Journal of African Studies, 2009)
Compartmentalizing time in order to engage with specific historical epochs and how they shaped African urban development, this paper turns to Tanure Ojaide’s, When It no Longer Matters Where You Live (1998), in order to explore the ripple effects and exilic implications of state neglect of postcolonial urbanscapes in the Niger Delta. More specifically, the paper engages with the author’s concern for the proverbial paradox of neglect of the oil-rich Niger Delta region of Nigeria by successive governments. Beyond the fact that the situation serves as a vector for the increasing consciousness of subnationalism in the region, the paper is concerned with the dynamics and the processes of migration that the situation produces either as overt transnational exile, or covert but thoroughly flawed postcolonial neologism of cosmopolitanism. I argue that the onus falls on the government to make conditions of urbanscapes in the homeland attractive and worth living for the retrieval of its human resources from the vortex of dispersal that has been exacerbated by globalization.